Early ERP Modulation for Task-Irrelevant Subliminal Faces - Pegna, Alan J.; Darque, Alexandra; Berrut, Claire; Khateb, Asaid (Frontiers in Psychology, 2011)
A number of investigations have reported that emotional faces can be processed subliminally, and that they give rise to specific patterns of brain activation in the absence of awareness. Recent event-related potential (ERP) studies have suggested that electrophysiological differences occur early in time (<200ms) in response to backward masked emotional faces. These findings have been taken as evidence of a rapid non-conscious pathway, which would allow threatening stimuli to be processed rapidly and subsequently allow appropriate avoidance action to be taken. However, for this to be the case, subliminal processing should arise even if the threatening stimulus is not attended. This point has in fact not yet been clearly established. In this ERP study, we investigated whether subliminal processing of fearful faces occurs outside the focus of attention. Fourteen healthy participants performed a line judgement task while fearful and non-fearful (happy or neutral) faces were presented both subliminally and supraliminally. ERPs were compared across the 4 experimental conditions (i.e., subliminal and supraliminal; fearful and non-fearful). The earliest differences between fearful and non fearful faces appeared as an enhanced posterior negativity for the former at 170ms (the N170 component) over right temporo-occipital electrodes. This difference was observed for both subliminal (p<.05) and supraliminal presentations (p<.01). Our results confirm that subliminal processing of fearful faces occurs early in the course of visual processing, and more importantly, that this arises even when the subject’s attention is engaged in an incidental task.